PELAKSANAAN PEMBINAAN PROFESIONALISME PAMONG BELAJAR DALAM PENINGKATAN KUALITAS PEMBELAJARAN KELOMPOK BELAJAR KESETARAAN - Sadid, Agus; Khairuddin, Khairuddin; Juariah, Siti (JIV-Jurnal Ilmiah Visi, 2008)
This qualitative research aimed at describing the efforts of the head of Learning Center to improve the tutors’ professionalism particularly in the Learning Centers for Equivalency. The research conducted in West Lombok and Sumbawa from February through April 2008. As a multicase study, the research found that the heads of Learning Centers have done all efforts to develop and build tutors’ professionalism, such as through intensive observation, lectures, in-service and pre-service trainings.